A formação de formadores por meio da arte - Silva, Vânia Maciel da (2017)
The object of study of this issue is an experience of continuous training carried out with coordinating teachers who train other teachers based on the contributions of art. Its main objective is to analyze the affections potentiated through art in the training environment. The methodology adopted follows the procedures of the art-based educational research (PEBA). The local of this issue is a public institution for the continuous training of teachers - the pedagogical nucleus of the education department of the State of São Paulo - where the coordinating teachers of the pedagogical nucleus, the formators of trainers, work. A constant and dynamic system that lasts throughout life, the teacher training emphasizes the recognition of the professional and personal knowledge generated by teachers in their daily work scenarios. Thus, the teacher training is somebody who faces obstacles being exposed to risks and divided between his fears and his challenges.He is subordinated to his judgment and perception. The author of this study, acting in this space as an art coordinating teacher, planned a process of formation for the trainers mediated by aesthetics. The theoretical contributions for the basis of this work were built on the literature review pertinent to the fields of art, aesthetics, education and teacher training. The ideas of Antonio Nóvoa, Andy Hargreaves, Elliot Eisner, Herbert Head, Ana Mae Barbosa, John Dewey, FaigaOstrower, and Rita Irwin focused the research. Possible by the contact with codes of art,the formation through aesthetic experience lead the formators to reflection and considerations of their practice in the educational environment with the perspective of a new way of thinking the formations.